Numerical and experimental investigations on a hybrid vertical axis wind turbine - Budea Sanda; Simionescu Ștefan-Mugur; Copăceanu Valentin (E3S Web of Conferences)
Wind energy represents one of the main sources of renewable energies. Innovation in wind turbine technology tends to focus on increasing energy production, especially at low wind velocities. Vertical axis wind turbines could have a greater expansion because they have many advantages, such as the capacity to start at low wind velocities and no need for orientation to the wind direction. The present paper analyses numerically and experimentally, a Savonius-Darrieus hybrid wind system on a common vertical shaft. CFD modeling and simulation show a slight instability at low velocities, up to entering the nominal working regime of 2-3 m/s, but also the separation of vortices and the fluid-blade interaction at over 9 m/s. At higher velocities, the performances and the power coefficients decrease, observations demonstrated also experimentally within the study. The optimal wind velocity for the Savonius-Darrieus vertical turbine is 6 m/s.